2012
DOI: 10.1111/j.1751-228x.2012.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Breakfast Skipping and School Performance in Adolescents

Abstract: Relation Between Breakfast Skipping 2 AbstractBreakfast skipping is common in adolescents, but research on the effects of breakfast skipping on school performance is scarce. This current cross-sectional survey study of 605 adolescents aged 11-18 years investigated whether adolescents who habitually skip breakfast have lower end of term grades than adolescents who eat breakfast daily. Additionally, the roles of sleep behavior, namely chronotype, and attention were explored. Results showed that breakfast skipper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 29 publications
3
37
0
1
Order By: Relevance
“…This is supported by evidence that demonstrates positive effects of breakfast on cognitive performance including attention and memory (Hoyland et al, 2009). Similarly, more on-task behavior in the classroom may be associated with improvements in academic performance supported by the positive association between habitual breakfast intake and academic performance (Boschloo et al, 2012;So, 2013). Moreover, an improvement in classroom behavior has the potential to reduce disruption and produce a more productive learning environment.…”
Section: Overview Of Findingssupporting
confidence: 48%
See 1 more Smart Citation
“…This is supported by evidence that demonstrates positive effects of breakfast on cognitive performance including attention and memory (Hoyland et al, 2009). Similarly, more on-task behavior in the classroom may be associated with improvements in academic performance supported by the positive association between habitual breakfast intake and academic performance (Boschloo et al, 2012;So, 2013). Moreover, an improvement in classroom behavior has the potential to reduce disruption and produce a more productive learning environment.…”
Section: Overview Of Findingssupporting
confidence: 48%
“…Frequency of breakfast consumption was associated with school performance in five studies. Breakfast skipping (eating breakfast <5 days/week) was associated with lower average annual school grades in a sample of 605 Dutch adolescents aged 11-18 years who were in higher educational streams (Boschloo et al, 2012). This association was evident in both sexes and independent of age.…”
Section: Intervention Studiesmentioning
confidence: 73%
“…Breakfast skipping (eating breakfast <5 days/week) was associated with lower average annual school grades in a sample of 605 Dutch adolescents aged 11–18 years who were in higher educational streams (Boschloo et al, 2012). This association was evident in both sexes and independent of age.…”
Section: Resultsmentioning
confidence: 99%
“…Because of having positive effects on appetite, hormonal and nervous signals, breakfast can control both appetite throughout a day and individuals weight (Leidy, Ortinau, Douglas, & Hoertel, 2013;Tin, Ho, Mak, Wan, & Lam, 2011). Studies have shown that students who eat breakfast do better than those who don't which is indicative of the importance of breakfast as a predictor of academic performance (Boschloo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%